Industrialization and the fertility decline - Raphaël Franck; Oded Galor (Brown University, Department of Economics, 2015)
The research provides the first empirical examination of the hypothesized effect of industrialization on the fertility decline. Exploiting exogenous source of regional variations in the adoption of steam engines across France, the study establishes that industrialization was a major catalyst in the fertility decline in the course of the demographic transition. Moreover, the analysis further suggests that the contribution of industrialization to the decline in fertility plausibly operated through the effect of industrialization on human capital formation. Thus, the study confirms one of the central elements of Unified Growth Theory which hypothesizes that a critical force in the transition from stagnation to growth was by the impact of industrialization on the onset of the demographic transition, via the rise in the demand for human capital.
Keywords: J10; N33; N34; O14; O33; 330; Economic Growth; Fertility Transition; Human Capital; Industrialization; Steam Engine